(3ehGQO GdCfGe aj TQM TQGjY GdESdGes - (3YHGS Hf Ydj Hf LYaQ, J(B1315(3g`s ((3eMeO Hf GdMSfs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3cJGH EMjGA GdehGJ hGdfXQ aj CWQGa CQHYI(B...s
(3BNQgG (B:s
(3hCeG HfGA Ydi GdeNJGQ ef LQjGf GdVeGf ajgG Ohf GdhOjYI ceG jXgQ eeG JbOe(B...s
(3aQZ ef JCdjag aj (B23 (3QHjY GdChd (B1304(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B:(3L(B23(3,U(B217(3,Qbe(B8687s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis